2017
DOI: 10.1016/j.celrep.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Depth of Cellular Quiescence by an Rb-E2F Network Switch

Abstract: Quiescence is a non-proliferative cellular state that is critical to tissue repair and regeneration. Although often described as the G0 phase, quiescence is not a single homogeneous state. As cells remain quiescent for longer durations, they move progressively deeper and display a reduced sensitivity to growth signals. Deep quiescent cells, unlike senescent cells, can still re-enter the cell cycle under physiological conditions. Mechanisms controlling quiescence depth are poorly understood, representing a curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
154
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(180 citation statements)
references
References 60 publications
(86 reference statements)
19
154
0
Order By: Relevance
“…Now, we have shown that, also in C. elegans , prolonged arrest delays blast cell divisions. This finding parallels that in cultured cells, where delayed reactivation of divisions after prolonged starvation is proposed to be due to quiescence deepening (Kwon et al, ). This suggests that blast cells in L1 larvae progress to deeper levels of quiescence throughout L1 arrest.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Now, we have shown that, also in C. elegans , prolonged arrest delays blast cell divisions. This finding parallels that in cultured cells, where delayed reactivation of divisions after prolonged starvation is proposed to be due to quiescence deepening (Kwon et al, ). This suggests that blast cells in L1 larvae progress to deeper levels of quiescence throughout L1 arrest.…”
Section: Discussionsupporting
confidence: 87%
“…Despite the lack of proliferation, quiescence is not a homogeneous state. Cells move progressively into a deeper level of quiescence over time (Kwon et al, ). As a consequence, the duration of quiescence affects cell viability and proliferation potential.…”
Section: Introductionmentioning
confidence: 99%
“…4B,C). These predictions corroborate with the recent experimental study performed by Kwon et al for the REF52 cell-type [38], where they had seen similar increase in the proportion of committed cells with increased pulse duration.…”
Section: Model Predicts the Outcome Of Several New Experiments Relatesupporting
confidence: 92%
“…EdU-Ki67+ NSCs) declined progressively and substantially with age, indicating that dormant NSCs were progressing into a deeper state of quiescence ( Figure 2B, C). This observation is consistent with the analysis of quiescence in fibroblast cultures (Kwon et al, 2017) and with recent modelling predictions and experimental data showing that NSCs in the adult ventricular-subventricular zone (V-SVZ) deepen their quiescence with age (Bast et al, 2018;Kalamakis et al, 2019;.…”
Section: Active Nscs Progressively Acquire the Capacity To Return To supporting
confidence: 91%
“…The deepening quiescence over time of dormant NSCs, which have not activated since the establishment of the DG niche, fits well with findings from in vitro studies of fibroblasts indicating that the depth of cellular quiescence is proportional to the time spent in quiescence (Kwon et al, 2017;Soprano, 1994). The transcriptional changes associated with a deeper quiescent state are typically an exaggeration of the changes that occur initially upon quiescence induction (Coller et al, 2006).…”
Section: Discussionsupporting
confidence: 77%